2019
DOI: 10.2139/ssrn.3524079
|View full text |Cite
|
Sign up to set email alerts
|

A Configurational View on Avatar Design – The Role of Emotional Attachment, Satisfaction, and Cognitive Load in Digital Learning

Abstract: In online learning settings interactive and meaningful feedback is becoming increasingly important. However, feedback from teachers is oftentimes missing in online learning settings. To overcome challenges that arise from the missing representation of teachers, our study analyzes the relevance of avatar designs in learning settings. We therefore rely on avatars as game design elements and analyze how their design can influence emotional attachment, learning process satisfaction, and extraneous cognitive load i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
(79 reference statements)
0
6
0
1
Order By: Relevance
“…A recent study showed that avatars (the most common form of virtual characters in gamification approaches) are among those game design elements that are least preferred by users of mHealth apps [ 42 ]. However, existing research has shown that the successful use of avatars in gamification approaches is complex and requires a profound consideration of individual user needs [ 43 ]. Only by incorporating these individual needs and avoiding one-size-fits-all solutions, a desired level of emotional attachment and extraneous cognitive load may be achieved [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that avatars (the most common form of virtual characters in gamification approaches) are among those game design elements that are least preferred by users of mHealth apps [ 42 ]. However, existing research has shown that the successful use of avatars in gamification approaches is complex and requires a profound consideration of individual user needs [ 43 ]. Only by incorporating these individual needs and avoiding one-size-fits-all solutions, a desired level of emotional attachment and extraneous cognitive load may be achieved [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, existing research has shown that the successful use of avatars in gamification approaches is complex and requires a profound consideration of individual user needs [ 43 ]. Only by incorporating these individual needs and avoiding one-size-fits-all solutions, a desired level of emotional attachment and extraneous cognitive load may be achieved [ 43 ]. Our results could be interpreted as an indicator that most developers of mHealth apps are not willing to put this effort into the development of virtual characters, especially because users seem to attach less importance to their inclusion in comparison to other game design elements.…”
Section: Discussionmentioning
confidence: 99%
“…It glows with everything") could have contributed to students' perception of personified traits, like friendliness, intelligence and trustworthiness, which were all rated highly. As discussed, personified traits in CAs could play a role in effective teaching interventions [48], especially since feelings of closeness and trust can enhance human teaching and learning experiences [2,5,63].…”
Section: Personificationmentioning
confidence: 99%
“…For instance, feelings of closeness with teachers have been shown to affect students' academic performance [2,5,63], which may also be the case when agents take on the teacher role. Another study indicates that the avatar used for pedagogical feedback-giving agents affect students' emotional attachment and satisfaction with the learning process [48], alluding to the potential for students' perception of agents to affect learning. Furthermore, research suggests understanding students' preconceptions and mental models can improve teaching [15,51].…”
Section: Introductionmentioning
confidence: 99%
“…B. über ein beginnendes Gespräch erfolgen: "Hallo Felix, du hast schon lange kein neues Material mehr erstellt" oder "Hallo Felix, du hast deinen letzten Beitrag noch nicht beendet". Andere Ansätze verwenden Gamification-Elemente wie Avatare, um die Benutzer zu motivieren (Schöbel et al 2019).…”
Section: Zweite Iteration Der Lehr-lernplattform Mit Chatbotunclassified